Kinship, Friendship, and Service Provider Social Ties and How They Influence Well-Being among Newly Resettled Refugees. (December 2019) - Greene, R. Neil
As refugees move from forced displacement to resettlement, their networks change dramatically alongside their living conditions and surroundings. The relative benefit of different kinds of ties in this context is not well known. Data for this study came from quantitative and qualitative interviews that were part of the Refugee Well-Being Project (N = 290), a longitudinal randomized controlled trial study inclusive of refugees resettling from the Great Lakes region of Africa, Afghanistan, Iraq, and Syria. Quantitative results revealed that greater numbers of kinship ties were related to better psychological quality of life ( p < .01) and greater numbers of reported services providers as social ties were related to higher emotional distress ( p < .001). Greater numbers of friendship ties were not statistically related to psychological quality of life or emotional distress. Qualitative findings suggest that cultural brokers—social ties that can bridge cultures, languages, and backgrounds—were particularly important to well-being, blending the benefits of strong and weak ties.